Diabetic Ephrin-B2-Stimulated Peripheral Blood Mononuclear Cells Enhance Poststroke Recovery in Mice - Rose Hilal; Marine Poittevin; Adrien Pasteur-Rousseau; Adrien Cogo; Gabrielle Mangin; Marie Chevauché; Yasmine Ziat; José Vilar; Jean-Marie Launay; Jean-François Gautier; Dong Broquères-You; Bernard I. Levy; et al. (Stem Cells International)
Clinical trials of cell therapy in stroke favor autologous cell transplantation. To date, feasibility studies have used bone marrow-derived mononuclear cells, but harvesting bone marrow cells is invasive thus complicating bedside treatment. We investigated the therapeutic potential of peripheral blood-derived mononuclear cells (PB-MNC) harvested from diabetic patients and stimulated by ephrin-B2 (PB-MNC+) (500,000 cells), injected intravenously 18–24 hours after induced cerebral ischemia in mice. Infarct volume, neurological deficit, neurogenesis, angiogenesis, and inflammation were investigated as were the potential mechanisms of PB-MNC+ cells in poststroke neurorepair. At D3, infarct volume was reduced by 60% and 49% compared to unstimulated PB-MNC and PBS-treated mice, respectively. Compared to PBS, injection of PB-MNC+ increased cell proliferation in the peri-infarct area and the subventricular zone, decreased microglia/macrophage cell density, and upregulated TGF-β expression. At D14, microvessel density was decreased and functional recovery was enhanced compared to PBS-treated mice, whereas plasma levels of BDNF, a major regulator of neuroplasticity, were increased in mice treated with PB-MNC+ compared to the other two groups. Cell transcriptional analysis showed that ephrin-B2 induced phenotype switching of PB-MNC by upregulating genes controlling cell proliferation, inflammation, and angiogenesis, as confirmed by adhesion and Matrigel assays. Conclusions. This feasibility study suggests that PB-MNC+ transplantation poststroke could be a promising approach but warrants further investigation. If confirmed, this rapid, noninvasive bedside cell therapy strategy could be applied to stroke patients at the acute phase.